Synthesis and evaluation of dinuclear cyclen-based lanthanide complexes for the hydrolysis of phosphodiester bonds - Moore, Doireann Á. (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
This thesis, entitled, "Synthesis and Evaluation of Cyclen-based Lanthanide Complexes for the Hydrolysis of Phosphodiester Bonds" is composed of five Chapters. In the first Chapter the structural importance of phosphodiester bonds in Nature and their cleavage by ribonucleases is introduced. The manipulation of the hydrolysis of such phosphodiester bonds using an artificial ribonuclease mimic for the development of a novel genetic therapy is outlined. The use of metal ions by ribonucleases, ribozymes, and artificial nucleases is examined and this is followed by a detailed discussion of recent advancements in the literature of metal based ribonuclease mimics, with a particular focus on the lanthanide metal ions. Finally, an overview of the work in this area by the Gunnlaugsson group is given and the work detailed in this thesis is briefly outlined.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.